High-efficiency transformation of amorphous carbon into graphite nanoflakes for stable aluminum-ion battery cathodes. Issue 26 (6th June 2019) - Tu, Jiguo; Wang, Junxiang; Li, Shijie; Song, Wei-Li; Wang, Mingyong; Zhu, Hongmin; Jiao, Shuqiang
Abstract : The highly efficient catalyst-free, eco-friendly and low-temperature graphitization process is a novel strategy for achieving the conversion of amorphous carbon precursors into graphite. Abstract : Highly efficient strategies for the transformation of amorphous carbon into graphite with high graphitization and crystallinity features have been significantly pursued in recent years; however, critical issues, including high processing temperature, insufficient graphitization, introduction of catalyst impurities, complicated post-purification procedures, and generation of greenhouse gas, still remain in traditional approaches. For significantly addressing these challenges, herein, a highly efficient catalyst-free, eco-friendly and low-temperature electrochemical transformation strategy was proposed for the preparation of highly graphitized porous graphite nanoflakes. Using inert SnO2 as an anode in CaCl2 -LiCl molten salts, the graphitization transformation of amorphous carbon materials could be realized at 700 °C, approaching the record in high-efficiency converting amorphous carbon to graphite; moreover, systematical analysis was performed to understand the electrochemical transformation of amorphous carbon into highly graphitized graphite nanoflakes. For extending their valuable applications, the as-prepared graphite nanoflakes were further utilized as cathodes in aluminum-ion batteries, which exhibited significantly promising energy storage performance; moreover, an initial discharge capacity of 63.6 mA h g −1 at a current density of 200 mA g −1 was achieved, which eventually became 55.5 mA h g −1 with a coulombic efficiency of 95.4% after 1000 cycles; thus, these cathodes exhibited stable long-term cycling performance. The combination of low-temperature electrochemical transformation and the subsequent high-performance applications of these nanoflakes in energy storage indicates that the proposed strategy is highly efficient for the transformation and utilization of abundant amorphous carbon resources for the realization of high value-added applications.